Hospital UiTM Puncak Alam tentatively will be opening in stages starting with the specialist clinic in October 2020 - UiTM, Hospital Puncak Alam (Hospital Puncak Alam, 2020)
Berita dan aktiviti Hospital UiTM Puncak Alam issue No 1/2020